2022
DOI: 10.1371/journal.pone.0268182
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Retzius-sparing versus conventional robot-assisted radical prostatectomy: A KSER update series systematic review and meta-analysis

Abstract: Background Robotic‐assisted radical prostatectomy(RARP) is widely used to surgically treat of localized prostate cancer. Among RARP, retzius-sparing techniques(RS-RARP) are implemented through douglas pouch, not the existing conventional approach(C-RARP). We conducted an updated systematic review and meta-analysis including recent published papers. Materials & methods Systematic review was performed following the PRISMA guideline. PubMed, EMBASE, and Cochrane Library were searched up to August 2021. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Notably, more than 20 publications in the latest 4 years were comprehensive, narrative, systematic, and or meta-analytic literature reviews of the studies comparing anterior (or standard) to posterior (or Retzius-sparing) prostatectomy. Table 2[29 ▪▪ ,30–33,34 ▪▪ ,35–39,40 ▪ ] summarizes the most important findings of the 11 systematic reviews, confirming the role of RS-RARP in providing better immediate urinary continence recovery. Some of these reviews confirmed the advantage of RS-RARP on late continence recovery.…”
Section: The (False?) Problem Of Positive Surgical Marginsmentioning
confidence: 67%
“…Notably, more than 20 publications in the latest 4 years were comprehensive, narrative, systematic, and or meta-analytic literature reviews of the studies comparing anterior (or standard) to posterior (or Retzius-sparing) prostatectomy. Table 2[29 ▪▪ ,30–33,34 ▪▪ ,35–39,40 ▪ ] summarizes the most important findings of the 11 systematic reviews, confirming the role of RS-RARP in providing better immediate urinary continence recovery. Some of these reviews confirmed the advantage of RS-RARP on late continence recovery.…”
Section: The (False?) Problem Of Positive Surgical Marginsmentioning
confidence: 67%
“…16 To date, eight systematic reviews and meta-analyses investigated the role of RS-RARP. [22][23][24][25][26][27][28][29] It merit mention the systematic review by Checcucci et al that reported comparable surgical outcomes and no significant difference in overall complications. 22 RS-RARP showed higher PSM rate (24% vs 15%), mainly in anterior tumors, but when the analysis was stratified for pT stage, there were similar rates for pT3 disease.…”
Section: Oncological and Functional Outcomesmentioning
confidence: 98%
“…Focusing on the pT3 subgroup, RS-RARP is superior to the conventional group in terms of continence recovery ( P = 0.047). It should be highlighted that the RS-RARP was associated with a high rate of positive surgical margin (PSM) in this advanced group of patients, OR = 0.74[0.55, 0.99] favoring non-Retzius sparing RARP [26]. Therefore, in high-risk localized diseases, RS-RARP should be offered with caution, even though there could be a potential benefit to continence outcomes [27].…”
Section: Retzius-sparing Approachmentioning
confidence: 99%